Phenylpyrazolone derivatives inhibit gastric emptying in rats by a capsaicin-sensitive afferent pathway - Vinagre,A.M. (2009)
Dipyrone (Dp), 4-aminoantipyrine (AA) and antipyrine (At) administered iv and Dp administered icv delay gastric emptying (GE) in rats. The participation of capsaicin (Cps)-sensitive afferent fibers in this phenomenon was evaluated. Male Wistar rats were pretreated sc with Cps (50 mg/kg) or vehicle between the first and second day of life and both groups were submitted to the eye-wiping test. GE was determined in these animals at the age of 8/9 weeks (weight: 200-300 g). Ten minutes before the study, the animals of both groups were treated iv with Dp, AA or At (240 μmol/kg), or saline; or treated icv with Dp (4 μmol/animal) or saline. GE was determined 10 min after treatment by measuring % gastric retention (GR) of saline labeled with phenol red 10 min after orogastric administration. Percent GR (mean ± SEM, N = 8) in animals pretreated with Cps and treated with Dp, AA or At (35.8 ± 3.2, 35.4 ± 2.2, and 35.6 ± 2%, respectively) did not differ from the GR of saline-treated animals pretreated with vehicle (36.8 ± 2.8%) and was significantly lower than in animals pretreated with vehicle and treated with the drugs (52.1 ± 2.8, 66.2 ± 4, and 55.8 ± 3%, respectively). The effect of icv administration of Dp (N = 6) was not modified by pretreatment with Cps (63.3 ± 5.7%) compared to Dp-treated animals pretreated with vehicle (62.3 ± 2.4%). The results suggest the participation of capsaicin-sensitive afferent fibers in the delayed GE induced by iv administration of Dp, AA and At, but not of icv Dp.